LTNE effects on binary nanofluid convection: A modified model. (2021) - Shukla, Shushant; Gupta, Urvashi; Devi, Mamta
Abstract: Double-diffusive convection problem for nanofluids is investigated under the effect of local thermal non-equilibrium (LTNE). A more realistic and effective modified model has been applied to consider the problem where volume fraction of nanoparticles is assumed to be invariable in primary state. Importance of the modified method lies in the fact that it considers both physical properties of nanoparticles i.e. density as well as conductivity for consideration of nanoparticle effects as compared to earlier models which were insensitive to the effects of conductivity of the nanoparticles. Three additional LTNE parameters have been introduced in the eigen value equation which play a remarkable role in the onset of nanofluid convection. To consider the impact of various parameters one term Gelerkin method is employed along with the use of Mathematica software for numerical computations. The LTNE parameters in the presence of solute significantly influence the critical wave number which was not true for LTE model.